Obstetric bleeding during the second half of pregnancy and childbirth : guidelines to practical training in obstetrics for higher education students of the 5th year Medical Faculty - Grishchenko, Olga Valentinivna; Kozub, Tetiana Olexandrivna; Грищенко, Ольга Валентинівна; Козуб, Тетяна Олександрівна (Kharkiv : V. N. Karazin Kharkiv National University, 2020)
The methodical recommendations contain a list of theoretical questions on the topic for independent preparation of students for practical training, a list of recommended and additional literature, as well as an example of test tasks.

Методичні рекомендації містять перелік теоретичних питань з даної теми для самостійної підготовки студентів до практичного заняття, список рекомендованої та додаткової літератури, а також приклад тестових завдань.
Акушерські кровотечі під час другої половини вагітності та у пологах : методичні рекомендації до практичних занять з акушерства для здобувачів вищої освіти V курсу медичного факультету
Навчальне видання
Keywords: SOCIAL SCIENCES::Social sciences::Education::Subject didactics; MEDICINE::Surgery::Obstetrics and women's diseases::Obstetrics and gynaecology; вагітність; кровотеча; передлежання плаценти; відшарування плаценти; розрив матки; pregnancy; bleeding; placental presentation; placenta detachment; uterine rupture